How do organizational routines paradoxically affect organizational innovation?. Issue 4 (23rd July 2020) - Lin, Haifen; Qu, Tingchen; Hu, Yanfang
Abstract : Purpose: This paper aims to address how organizational routines paradoxically affect the process of organizational innovation based on a new construct of routines or to investigate the coexistence of both hindering and promoting effects from routines and their differentiated affecting paths. Design/methodology/approach: This paper adopts an interpretive and exploratory case study on the business model innovation of Yimu Technology Company Limited (Yimu Tech) from product standardization to customization. Considering that this innovation reflects a successful down-up rather than traditional up-down innovation, this paper focuses on it to explore how the most micro routines affect the whole process of innovation. Almost two years were spent in collecting data from Yimu Tech and in following the innovation through approaches of semi-structured interviews, archival data and observation; the data were analyzed through a five-step process before a framework showing the paradoxical effects was finally set up. Findings: This research specifies the construct of organizational routines and promotes a five-dimensional concept covering the organizational, collective and individual levels of an organization. It confirms the interaction between the performative and ostensive aspects of routines, by showing that the ostensive aspect may not only guide tasks performing but also allow multiple changes, and the performative aspect may affect the ostensive aspect through the down-up or up-down path. Also, it finds that routines may paradoxically affect all three phases of innovation, with a strong up-down hindering effect but a weak down-up promoting effect in the preparation phase, a strong down-up promoting effect but a weak hindering effect in the emergence phase and both significant effects in the consolidation phase. Research limitations/implications: This research is constrained by several limitations. The set up framework of routines and their paradoxical effects on innovation need a further confirmation in more contexts or organizations; more elements should be considered in exploring the evolution of routines and their effects on innovations; little attention has been paid to the relationship between these two types of effects, conflicting with each other, joining together or working independently. Originality/value: The findings offered some valuable insights for further research on organizational routines and organizational innovation and hold important implications for management practices. This research enriched the two-aspect view of routines by constructing a five-dimensional framework; further research studies on routine dynamics by showing the interaction between the performative and ostensive aspects can contribute to the study on effects of organizational routines on innovations by showing how routines promote and hinder innovation simultaneously throughout the whole process. It reminds managers of the strong power from the microlevel of an organization in innovation.